Feasibility of colorectal endoscopic submucosal dissection (ESD) carried out by endoscopists with no or little experience in gastric ESD. (20th April 2017) - Shiga, Hisashi; Ohba, Reina; Matsuhashi, Tamotsu; Jin, Mario; Kuroha, Masatake; Endo, Katsuya; Moroi, Rintaro; Kayaba, Shoichi; Iijima, Katsunori
Abstract : Background and Aim: Colorectal endoscopic submucosal dissection (ESD) is recommended to be carried out only by endoscopists with sufficient experience in gastric ESD. However, early gastric carcinoma is less common in Western countries than in Japan, and endoscopic maneuverability differs between the stomach and colorectum. We assessed the feasibility of colorectal ESD carried out by endoscopists with no or little experience in gastric ESD. Methods: We analyzed en bloc resection, R0 resection and perforation rates in 180 consecutive colorectal ESD carried out by three endoscopists who had no or <5 cases of experience in gastric ESD. We also identified factors associated with R0 resection failure. Results: Overall en bloc and R0 resection rates were 93.3% (168/180) and 82.2% (148/180), respectively. All 11 cases with perforation were treated endoscopically. Dividing 180 cases into three learning phases (early, middle, or late phases), the en bloc and R0 resection rates increased from 88.3% and 75.0% in the early phase to 98.3% and 88.3% in the late phase, respectively. Perforation rate also improved from 10.0% to 3.3%. Factors associated with R0 resection failure were location at junctions (odds ratio: 6.8, 95% CI: 1.9–27.5), preoperative factors reflecting fibrosis (5.8, 1.9–19.0), and late phase (0.2, 0.1–0.7). Conclusion: Endoscopists without experience in gastric ESD carried out colorectal ESD safely. In the early and middle phases (≤40 cases), they should treat mainly rectal lesions but may also resect lesions in the colon avoiding flexures. Lesions located at junctions and those with preoperative factors reflecting fibrosis should be resected after completing 40 procedures.